An ontology-based framework for bioinformatics workflows. (5th September 2007) - Digiampietri, Luciano A.; Perez-Alcazar, Jose de J.; Medeiros, Claudia Bauzer
The proliferation of bioinformatics activities brings new challenges ? how to understand and organise these resources, how to exchange and reuse successful experimental procedures, and to provide interoperability among data and tools. This paper describes an effort toward these directions. It is based on combining research on ontology management, AI and scientific workflows to design, reuse and annotate bioinformatics experiments. The resulting framework supports automatic or interactive composition of tasks based on AI planning techniques and takes advantage of ontologies to support the specification and annotation of bioinformatics workflows. We validate our proposal with a prototype running on real data.